2002
DOI: 10.1177/107327480200900206
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccines for Hematologic Malignancies

Abstract: Active immunization using current cancer vaccine approaches is feasible and safe. Although no major successes have been reported, the positive clinical results observed in some patients support the potential for therapeutic cancer vaccination in the management of hematologic malignancies. Results of studies that are testing vaccine formulations, targets, and settings (eg, bone marrow transplantation) may support the use of cancer vaccination as an efficient therapeutic strategy against tumors of hematologic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 95 publications
0
15
0
1
Order By: Relevance
“…The ease of tumour accessibility, the ability of current treatments to achieve a minimal residual state that could be accurately monitored, and the ability of myeloid cells to differentiate in vitro to functional dendritic cells combine to facilitate any intent to generate successful immonotherapeutic strategies (Borrello & Sotomayor, 2002). Therefore, provided a suitable tumour target/s is/are chosen, immunotherapy for haematological malignancies should provide the lead for further development of tumour vaccines.…”
Section: Future Directionsmentioning
confidence: 99%
“…The ease of tumour accessibility, the ability of current treatments to achieve a minimal residual state that could be accurately monitored, and the ability of myeloid cells to differentiate in vitro to functional dendritic cells combine to facilitate any intent to generate successful immonotherapeutic strategies (Borrello & Sotomayor, 2002). Therefore, provided a suitable tumour target/s is/are chosen, immunotherapy for haematological malignancies should provide the lead for further development of tumour vaccines.…”
Section: Future Directionsmentioning
confidence: 99%
“…To our knowledge there are no published data on clinical studies using cell-based vaccines in lymphoma, although an ongoing phase I clinical trial study of immunotherapy with autologous tumor cell vaccine and interleukin-2 has been reported [68]. This trial was conducted to assess the safety of immunotherapy with autologous tumor cell vaccine and interleukin-2 in patients with stage III, IV, or recurrent follicular lymphoma; to determine the clinical response of patients treated with this regimen; and to assess the immune response of patients treated with this vaccine.…”
Section: Clinical Studiesmentioning
confidence: 95%
“…Unique tumor-associated antigens may include bcr/abl peptides in CML, AML/ETO or PMLRARa in acute myeloid leukemia (AML). 4,5 Furthermore, idiotypic specific immunoglobulins may act as tumor specific antigens in B-cell lymphoma. 6,7 Mutated oncogenes like P53 and RAS may be expressed in many tumors.…”
Section: Tolerance To Hematological Malignanciesmentioning
confidence: 99%